The united stated drone strikes in Pakistan and violation of humanitarian laws - Imran, Muhammad; Nordin, Rohaida; Muhamad, Mohd Munzil; Idrees, Rao Qasim (2017)
Purpose - After the incident of 9/11, the use of unmanned combat aerial vehicle, also known as combat drone in armed conflicts among States, non-state actors, disruptive groups and organizations has increased and expanded.Combat drones are controlled by operators who depend on the information obtained from cameras and sensors which are the primary sources of information needed for purposes of launching any strikes. Drone strikes hit their targets without any identification process therefore many innocent people are killed.Drone strikes launched at non-conflict area also increases concern about illegitimate interference of State’s territorial sovereignty and issue of violation of international laws. This paper aims at critically reviewing and evaluating incidences of the United States’ combat drone strikes in Pakistan.In particular, this paper reviews the damage caused to innocent people through drone strikes and identifies any possible violations of international laws.It also examines to what extent the strikes diminishing the sovereignty of Pakistan.